Mapping Polar Bear Maternal Denning Habitat in the National Petroleum Reserve–Alaska with an IfSAR Digital Terrain Model - Durner, George M.; Simac, Kristin; Amstrup, Steven C. (ARCTIC, 2013)
The National Petroleum Reserve–Alaska (NPR-A) in northeastern Alaska provides winter maternal denning habitat for polar bears (Ursus maritimus) and also has high potential for recoverable hydrocarbons. Denning polar bears exposed to human activities may abandon their dens before their young are able to survive the severity of Arctic winter weather. To ensure that wintertime petroleum activities do not threaten polar bears, managers need to know the distribution of landscape features in which maternal dens are likely to occur. Here, we present a map of potential denning habitat within the NPR-A. We used a fine-grain digital elevation model derived from Interferometric Synthetic Aperture Radar (IfSAR) to generate a map of putative denning habitat. We then tested the map’s ability to identify polar bear denning habitat on the landscape. Our final map correctly identified 82% of denning habitat estimated to be within the NPR-A. Mapped denning habitat comprised 19.7 km2 (0.1% of the study area) and was widely dispersed. Though mapping denning habitat with IfSAR data was as effective as mapping with the photogrammetric methods used for other regions of the Alaskan Arctic coastal plain, the use of GIS to analyze IfSAR data allowed greater objectivity and flexibility with less manual labor. Analytical advantages and performance equivalent to that of manual cartographic methods suggest that the use of IfSAR data to identify polar bear maternal denning habitat is a better management tool in the NPR-A and wherever such data may be available. La réserve pétrolière nationale–Alaska (NPR-A), située dans le nord-est de l’Alaska (NPR-A), constitue un habitat hivernal de tanières de mise bas pour l’ours polaire (Ursus maritimus) et présente de grandes possibilités du point de vue des hydrocarbures récupérables. Les ours polaires des tanières qui sont exposés aux activités de l’être humain peuvent abandonner leur tanière avant que leurs petits ne soient prêts à survivre les rigueurs de l’hiver de l’Arctique. Afin de faire en ...